Relative Age Effects and Gender Differences in the National Test of Numeracy: A Population Study of Norwegian Children - Aune, Tore K.; Ingvaldsen, Rolf P.; Vestheim, Ole P.; Bjerkeset, Ottar; Dalen, Terje (Frontiers in Psychology, 2018)
Abstract Relative age effect (RAE) refers to the phenomenon by which children born early in their year of birth perform more highly than children born later in the same cohort. The purpose of this study was to evaluate whether an RAE exists in the Norwegian numeracy test for 5th, 8th and 9th graders (National sample of 175,760). The results showed that the RAE is consistent across 5th, 8th and 9th graders for both boys and girls. Mean scores decreased systematically with month of birth for both genders, and the mean scores for boys were higher compared with girls. The most interesting result and novelty is the gender difference in RAE observed analysing high- vs low scorers. Boys born early in the year were overrepresented as high scorers (RAE advantage), whereas girls born late in the year were overrepresented as low scorers (RAE disadvantage). It would be beneficial for researchers, teachers and education policymakers to be aware of RAE, both in terms of the practical use and implications of test results and to help identify strategies to adjust for relative age differences in national tests.